2023
DOI: 10.47836/pjssh.31.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Online Activities and Technology Use Among Older Adults in Thailand

Tanpat Kraiwanit,
Kris Jangjarat,
Areeya Srijam

Abstract: In the digital era, the use of technological tools and platforms has become increasingly prevalent among people, including older adults, for various daily activities such as social interactions, online payments or shopping, entertainment, and information seeking. The prudent use of technology by older adults provides several benefits, allowing them to undertake useful or convenient activities easily. Moreover, older adults with functional and up-to-date technological skills have better employment prospects, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…In this study, using TikTok was strongly associated with an increased impact of the Starlink project on legal systems, regulations, and national security in Thailand, with an increase of 8.117. The results were in line with a study conducted by Kraiwanit et al (2023), which examined the factors influencing the online activities of older Thai adults. The findings revealed that participation in online activities is influenced by various factors, including the choice of online media platform.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, using TikTok was strongly associated with an increased impact of the Starlink project on legal systems, regulations, and national security in Thailand, with an increase of 8.117. The results were in line with a study conducted by Kraiwanit et al (2023), which examined the factors influencing the online activities of older Thai adults. The findings revealed that participation in online activities is influenced by various factors, including the choice of online media platform.…”
Section: Discussionsupporting
confidence: 90%